ANALISIS PEMASARAN JAGUNG HIBRIDA DI DESA BATUPUTIH KECAMATAN BATURAJA BARAT KABUPATEN OGAN KOMERING ULU - Agneseta Rantika Winduandini; endang lastinawati (JASEP, 2022)
This study aims to determine income and find out marketing channel for hybrid corn farmers in Batuputih Village, Baturaja District West Ogan Komering Ulu Regency, is it efficient or not. Method research that is used in this study is a survey method. Method sampling used in this study is the snowball method. The results showed that the income of hybrid corn farmers in Batuputih Village is very good and adequate, the marketing channels are in accordance with the marketing process, namely from farmers to village collectors to factories to traders retailers then to consumers, and marketing of hybrid corn in Batuputih village already efficient.Keyword: Efficient, Corn, Marketing, Channel